DESAIN MANAJEMEN PENDIDIKAN KARAKTER DI MADRASAH - Novan Ardy Wiyani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2012)
Abstract : Madrasah as institution of education is a noble industry. Madrasah has double missions, there are profit mission and social mission. Unfortunately madrasah has been doing education process overcognitifly and ignore moral aspect, that fact is a problem in madrasah. Caused by it a concept of character education must be implementated in madrasah through management desain of character education in madrasah. In this article, author explains how to implementate management desain of character education in madrasah. There are four components that concerned in it. Key Words: Management, Character Education, Teachers, Curicullum, and Culture.